2019
DOI: 10.1002/cbin.11221
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mechanical vibration on cell morphology, proliferation, apoptosis, and cytokine expression/secretion in osteocyte‐like MLO‐Y4 cells exposed to high glucose

Abstract: Diabetic patients exhibit significant bone deterioration. Our recent findings demonstrate that mechanical vibration is capable of resisting diabetic bone loss, whereas the relevant mechanism remains unclear. We herein examined the effects of mechanical vibration on the activities and functions of osteocytes (the most abundant and well‐recognized mechanosensitive cells in the bone) exposed to high glucose (HG). The osteocytic MLO‐Y4 cells were incubated with 50 mM HG for 24 h, and then stimulated with 1 h/day m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 65 publications
2
6
0
Order By: Relevance
“…They also noted that the anabolic effect of mechanical stimulation was enhanced with the incorporation of resting period between loadings. These findings were replicated by Sun et al (2019) who showed that MLO-Y4 osteocyte like cells stimulated by 45 Hz at 0.5 g promoted the secretion of prostaglandin E 2 and OPG, and inhibited the secretion of tumor necrosis factor-α and RANKL [ 212 ]. Tanaka et al (2003) found similar results testing osteoblasts in vitro with vibration [ 213 ].…”
Section: Musculoskeletal Effectsmentioning
confidence: 73%
“…They also noted that the anabolic effect of mechanical stimulation was enhanced with the incorporation of resting period between loadings. These findings were replicated by Sun et al (2019) who showed that MLO-Y4 osteocyte like cells stimulated by 45 Hz at 0.5 g promoted the secretion of prostaglandin E 2 and OPG, and inhibited the secretion of tumor necrosis factor-α and RANKL [ 212 ]. Tanaka et al (2003) found similar results testing osteoblasts in vitro with vibration [ 213 ].…”
Section: Musculoskeletal Effectsmentioning
confidence: 73%
“…More importantly, osteocytes are found to be a powerful mechanosensor and mechanotransducer, which can orchestrate bone remodeling by the secretion of cytokines though their long dendritic processes to regulate osteoblast and osteoclast activities (e.g., sclerostin and RANKL) (37). Several previous studies have found that high glucose exposure decreases osteocyte viability and increases sclerostin expression (a negative regulator of bone formation) (38,39). Similarly, radiation has also been reported to impair osteocyte survival in rodents (40).…”
Section: Discussionmentioning
confidence: 99%
“…The pore pressure gradient [ 2 , 3 ], solute transport [ 4 , 5 ], and fluid shear stress generated by the fluid flow are considered to be significant biomedical signals for osteocyte mechanotransduction in situ [ 6 8 ]. Osteocytes are the most sensitive bone cell type that are considered as mechanosensors within bone that can sense mechanical stimulations and transduce them into biochemical signals [ 9 ], thereby regulating bone remodeling [ 10 12 ]; however, whether and how these factors generated by the fluid flow as a flow sensor to activate the native osteocyte remains unclear [ 13 ]. Strain amplification effect on osteocyte membrane may produce a less osteogenic than response than fluid flow [ 14 ], and some studies have suggested that the fluid flow shears the osteocyte membranes or induces cytoskeleton deformation to elicit biochemical responses [ 1 , 6 , 8 , 15 ].…”
Section: Introductionmentioning
confidence: 99%